KEBIJAKAN RAPID TEST DRIVE THRU OLEH PEMERINTAH DAERAH PROVINSI JAWA BARAT - Galuh Pravita Nunsi; Karin Agustin Gusa (Jurnal Kebijakan Pemerintahan, 2020)
This study aims to see the extent to which the West Java Regional Government applies a policy of rapid test drive thru located in Gedung Sate and Bandung City Hall. The rapid test drive thru technique is done inside the vehicle without having to get out of the vehicle. This research uses a qualitative method with a description model (event). Retrieval of data sourced from secondary data conducted through social media. The results of this study indicate that there are still obstacles that occur in the application of rapid test drive thru. Keywords : Policy, Rapid Test Drive Thru, Covid-19